Hypnotizability and Catechol-O-Methyltransferase (COMT) polymorphysms in Italians - Presciuttini, Silvano; Gialluisi, Alessandro; Barbuti, Serena; Curcio, Michele; Scatena, Fabrizio; Carli, Giancarlo; Santarcangelo, Enrica L. (Frontiers in Human Neuroscience, 2014)
Higher brain dopamine content depending on lower activity of Catechol-O-Methyltransferase (COMT) in subjects with high hypnotisability scores (highs) has been considered responsible for their attentional characteristics. However, the results of the previous genetic studies on association between hypnotisability and the Catechol-O-Methyltransferase (COMT) single nucleotide polymorphism (SNP) rs4680 (Val158Met) were inconsistent. Here, we used a selective genotyping approach to re-evaluate the association between hypnotisability and COMT in the context of a two-SNP haplotype analysis, considering not only the Val158Met polymorphism, but also the closely located rs4818 SNP. An Italian sample of 53 highs, 49 low hypnotizable subjects (lows) and 57 controls, were genotyped for a segment of 805 bp of the COMT gene, including Val158Met and the closely located rs4818 SNP. Our selective genotyping approach had 97.1% power to detect the previously reported strongest association at the significance level of 5%. We found no evidence of association at the SNP, haplotype and diplotype levels. Thus, our results challenge the dopamine-based theory of hypnosis and indirectly support recent neuropsychological and neurophysiological findings reporting the lack of any association between hypnotisability and focused attention abilities.